BLOOD GASES AND ELECTROLYTES UNDER USE OF MAGNETITE NANOPARTICLES IN BLOOD LOSS - Vazhnichaya, E.M.; Lutsenko, R.V.; Semaka, O.V.; Deviatkina, T.O.; Deviatkina, N.M.; Kurapov, Yu.A.; Litvin, S.Ye. (World of Medicine and Biology, 2021)
Blood gases, acid-base balance, and electrolytes were studied under the conditions of correction of acute blood loss in abino rats with magnetite nanoparticles (5–8 nm) obtained by electron-beam technology and incorporated into sodium chloride crystals. It was shown that blood loss decreases total hemoglobin and the volumetric concentration of oxygen, diminishes sodium concentration and increases potassium concentration in the blood. Dissolved and injected intraperitoneally after the blood loss, magnetite nanoparticles (1.35–6.75 mg iron/kg) reduce the partial pressure of carbon dioxide, increase the partial pressure of oxygen, saturation of hemoglobin with oxygen and volumetric oxygen concentration, increase hydrogen index and sodium content, and reduce potassium concentration in the blood. These positive changes develop against the background of an increase in total hemoglobin. They surpass some effects of the traditional iron preparation and can be the basis for further research aimed at the use of magnetite nanoparticles in acute posthemorrhagic syndrome.
Keywords: blood gases; electrolytes; acid-base balance; blood loss; magnetite nanoparticles